Imipramine, Ulcerative Colitis and Linear Iga Bullous Dermatosis - : A Curious Triad - Rostad, Kylie (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.